Role of innovation, creativity and intellectual property in start-up businesses and proposed some solutions for Hanoi - Khong Quoc Minh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
Today, start-up is a term commonly used with the implication that start-up businesses are based on exploiting intellectual property, technology, and new business models. This article provides another perspective on start-up and innovation, creativity. The article also clarifies the issue of intellectual property for innovation, creativity in start-up businesses. Aspects of innovation, creativity and intellectual property, the article initially evaluates the current status of start-up businesses in Hanoi, Vietnam and proposes some suggested solutions for Hanoi. Code: 24062101